Kinship and social organisation - Rivers, W. H. R. (William Halse Rivers), 1864-1922 (Cornell University Library, 2011)
Originally published in 1914. This volume from the Cornell University Library's print collections was scanned on an APT BookScan and converted to JPG 2000 format by Kirtas Technologies. All titles scanned cover to cover and pages may include marks notations and other marginalia present in the original volume.